Analisis Nilai Tambah dan Strategi Pengembangan Ubi Jalar sebagai Bahan Pangan Subtitusi Tepung Terigu di Kabupaten Mojokerto, Jawa Timur - Dini Nafisatul Mutmainah; Ahmad Haris Hasanuddin Slamet; Sekar Ayu Wulandari (JURNAL AGRIBISNIS, 2026)
Sweet potato is a local commodity with great potential for development into alternative flour due to its abundant raw material availability and good nutritional content. This study aimed to analyze the added value of sweet potato processing into local flour and formulate a development strategy as a food substitute for wheat flour in Mojokerto Regency, East Java. The research method used was descriptive and analytical with quantitative and qualitative approaches. The value-added analysis was conducted using the Hayami method, while the development strategy formulation was analyzed using the SWOT method. The results showed that processing sweet potato into local flour produces an added value of IDR 22,000/kg with a value-added ratio of 62.85% and a profit level of 98.66%, indicating that this business is feasible and economically profitable. Based on the SWOT analysis, recommended development strategies include increasing product promotion, developing healthy food-based product innovations, gradual technology investment, and strengthening consumer education. Overall, the development of sweet potato flour has the potential to increase the economic value of local commodities while supporting national food security.